Identification of the cellular targets of the transcription factor TCERG1 reveals a prevalent role in mrna processing - Pearson, J.L. (2008)
The transcription factor TCERG1 (also known as CA150) associates with RNA polymerase II holoenzyme and alters the elongation efficiency of reporter transcripts. TCERG1 is also found as a component of highly purified spliceosomes and has been implicated in splicing. To elucidate the function of TCERG1, we used short interfering RNA-mediated knockdown followed by en masse gene expression analysis to identify its cellular targets. Analysis of data from HEK293 and HeLa cells identified high confidence targets of TCERG1. We found that targets of TCERG1 were enriched in microRNA-binding sites, suggesting the possibility of post-transcriptional regulation. Consistently, reverse transcription-PCR analysis revealed that many of the changes observed upon TCERG1 knockdown were because of differences in alternative mRNA processing of the 3′-untranslated regions. Furthermore, a novel computational approach, which can identify alternatively processed events from conventional microarray data, showed that TCERG1 led to widespread alterations in mRNA processing. These findings provide the strongest support to date for a role of TCERG1 in mRNA processing and are consistent with proposals that TCERG1 couples transcription and processing. © 2008 by The American Society for Biochemistry and Molecular Biology, Inc.